Development Of Multi-Component Loads, Torque And Temperature Measurement Device For Friction Stir Welding Process - Khairuddin, Jauhari Tahir. (2013)
Friction stir welding process is a solid state joining method that utilizes heat source from mechanical friction work of a rotational tool exerted on work material, producing joint without the use of filler material. Since its introduction, friction stir welding is still at infant stage compared to conventional fusion joining method. The welding process fundamental is still not well established, lack in standard practicing guideline and optimum operating conditions for typical material application as well as inability to definitively relate process variables to the produced joint properties. The basis of this study is regarding to the mechanical work principle of the welding process, which is devised through measurement method as a mean to look for the possible benefits of improved joint mechanical properties. This study presents the analysis of welding parameters responses via a metrology system which measure the dynamic and quasi-static multi components three dimensional loads, torque exerted and to capture the corresponding temperature profile. The measured loads and torque represent the acting reaction forces suggesting its influences on joint physical properties based on welding parameters variables. In addition, a mathematical model is derived to approximate the welding process based on the work material temperature-dependent material properties, employed to validate the metrology system. Contact mechanic principle is adapted into the model accounting both Coulomb’s friction and plastic deformation principle. Proceeding, heat transfer within the system is studied through experimental work. The relationship of the measured loads and torque with the corresponding temperature shows the possibility to control the process variables.